2018
DOI: 10.1149/2.007189jes
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetic Properties of the Passive Film on Copper in the Presence of Sulfate-Reducing Bacteria

Abstract: Copper specimens were exposed to Sulfate-Reducing Bacteria (SRB) for 10 months under the conditions corresponding to the final disposal of high-level nuclear waste. In-situ electrochemical impedance spectroscopy (EIS) measurements were carried out to characterize the surface-environment interface after various times of exposure. The EIS results are interpreted in terms of the Point Defect Model (PDM), in order to obtain kinetic information on the formation of the Cu 2 S passive film. The standard rate constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 41 publications
(69 reference statements)
4
37
0
Order By: Relevance
“…Rather, the corrosion product will remain porous, such that incoming sulfide will be able to continuously react at the copper surface. Some counterarguments have been raised about this description, suggesting the films may be passive, [ 33 ] and these questions have been clarified, [ 34 ] rebutted, [ 35 ] and further debated. [ 36 ] The most recent experimental and mechanistic analyses do not support the existence of a barrier film [ 37 ] ; thus, the description of a passive sulfide film does not enter safety arguments for SKB [ 38 ] or the NWMO.…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
“…Rather, the corrosion product will remain porous, such that incoming sulfide will be able to continuously react at the copper surface. Some counterarguments have been raised about this description, suggesting the films may be passive, [ 33 ] and these questions have been clarified, [ 34 ] rebutted, [ 35 ] and further debated. [ 36 ] The most recent experimental and mechanistic analyses do not support the existence of a barrier film [ 37 ] ; thus, the description of a passive sulfide film does not enter safety arguments for SKB [ 38 ] or the NWMO.…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
“…Passive film properties are described in terms of the point defect model and evidence for film breakdown and pitting have been presented. [ 34–39 ] The observation of a levelling off of the anodic current with increasing potential during cyclic voltammetry is consistent with passive behaviour, [ 37 ] although the observed current is the same on the forward and reverse potential scans, which would not be expected if a passive film had been formed on the forward scan. [ 41 ] Martino et al [ 41 ] also suggested that the reported film breakdown events [ 34,36 ] were instead the onset of rapid anodic dissolution of copper as CuCl 2 − species through a porous Cu 2 S film.…”
Section: Canister Evolutionmentioning
confidence: 63%
“…One example of this difference between laboratory and repository conditions relates to the properties of the Cu 2 S formed on copper in sulphide‐containing environments. There has been a recent debate in the literature about whether these films should be classified as passive [ 34–39 ] or porous. [ 1–4, 40,41 ] Although there is no strict definition of a passive versus a porous film, the important distinction here is that passive films could be subject to localised breakdown and pitting, [ 34–37 ] whereas a copper surface covered by a porous film would tend to corrode relatively uniformly.…”
Section: Canister Evolutionmentioning
confidence: 99%
“…The general solution of the ODE was obtained by introducing expressions (25) and (26) in (24). Then, using the initial condition, the value of was determined; obtaining in this way the unique solution of the Cauchy problem.…”
Section: Solution Of the Cauchy Problemmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) is a non-destructive electrochemical method, with a broad range of applications in different fields of electrochemical science and engineering, among which are, for example, energy storage [1][2], batteries [3][4][5][6][7][8], electrochemical sensors [9][10][11][12], fuel cells [13][14][15][16][17][18], electrolysers [19][20][21], corrosion and coatings [22][23][24][25], and bioelectrochemistry [26,27]. The power of this electrochemical technique arises from its ability to distinguish the different physicchemical processes undergoing at different timescales in the system [28].…”
Section: Introductionmentioning
confidence: 99%